The Effect of Silica (SiO2) to the Severity of Yellow Leaf Curl Disease on Chili Pepper - Dewa Gede Wiryangga Selangga; Sri Hendrastuti Hidayat; Anas Dinurrohman Susila; Suryo Wiyono (Jurnal Perlindungan Tanaman Indonesia, 2019)
Yellow leaf curl disease of chili pepper caused by Pepper yellow leaf curl virus (PYLCV) has been reported as an important disease in Java and Bali. Disease severity reached 80−100% and it may cause significant yield losses. In order to reduce the negative impact of synthetic insecticides, silica application was evaluated for its potency to suppress the disease. A greenhouse experiment was conducted using randomly block design with 2 factors: PYLCV isolate (Java and Bali) and silica (SiO2) treatment (with and without). Parameters observed were disease symptoms, incubation period, disease incidence and severity, and total silica level. The symptoms of virus infection in Pelita 8 and Seret cultivars were yellow mosaic, leaf curl, green mosaic, dwarf, and cupping upward or downward. A Specific DNA fragment of 912 bp was successfully amplified from 4 samples. Four sequences were obtained and further analysis showed their highest homology, i.e. 96% and 97% with Pepper yellow leaf curl Indonesia virus-Java (PYLCIV-Java) (JX416180) and PYLCIV-KrthAl (LC381274), respectively. Infection by different virus isolates did not affect disease severity significantly. The application of silica was able to delay symptom development and to suppress the severity of the disease in the range of 16.67−30.33%. Silica application on the soil increased the total content of silica in the plants. However, a further experiment is required to understand the mode of action of silica in inducing plant resistance to the pathogen.